Cryopreservation of invitro-propagated protocorms of Caladenia for terrestrial orchid conservation in Western Australia - Watanawikkit, P.; Tantiwiwat, S.; Bunn, E.; Dixon, Kingsley; Chayanarit, K. (2012)
Cryopreservation is an important tool for the exsitu preservation of endangered plants. In this article, we describe the development of a cryopreservation protocol for orchid protocorms using the terrestrial Australian species Caladenia latifolia. Protocorms of C. latifolia generated asymbiotically each month on Murashige and Skoog (MS) medium containing 10µM N6-benzyladenine (BAP) provided explant sources for cryopreservation. Three size classes of protocorms were used as source explant material [small (S, =1mm); medium (M, >1<4mm); large (L, =4mm)] in combination with five desiccation treatments, i.e. 0, 0.4, 0.6, 0.8 and 1.0M glycerol. After 2days on desiccation medium, protocorms were treated with two cryoprotectant solutions (PVS2 and PVS4 at 0°C for 15, 20, 25 and 30min) before immersion in liquid nitrogen for 1day. Protocorms were then removed from liquid nitrogen storage, warmed rapidly (in a 40°C waterbath) and placed on three recovery media: half-strength MS with 0.5µM BAP, 0.5µM 6-furfurylaminopurine (kinetin) or 0.5µM 1-phenyl-3-(1,2,3-thiadiazol-5-yl)-urea (TDZ). Protocorms on recovery media were incubated at 25°C under dark conditions and potential protocorm survival was observed at 60 and 90days using a fluorescein diacetate (FDA) test for protocorm viability. Protocorm survival was correlated significantly with explant size. Large cryopreserved protocorms had the highest potential survival rate (>90%) relative to small (<10%) and medium (70-80%) protocorms. Different desiccation media treatments did not affect significantly the survival percentage (74-92%). Similarly, changing the cryoprotectant solution and time of incubation at 0°C did not affect significantly potential protocorm survival (76-96%). Potential protocorm survival on various recovery media was not significantly different among treatments (88-100% survival). The study indicates that the cryopreservation of terrestrial orchid protocorms is technically feasible and provides a new and potentially highly beneficial tool in terrestrial orchid conservation where seed may be limited (because of species rarity), or as a means of storing and later utilizing the large surpluses of protocorms generated in propagation programmes.